A systematic review and meta-analysis of suicidality in psychotic disorders: Stratified analyses by psychotic subtypes, clinical setting and geographical region. (December 2022) - Álvarez, Aida; Guàrdia, Armand; González-Rodríguez, Alexandre; Betriu, Maria; Palao, Diego; Monreal, José Antonio; Soria, Virginia; Labad, Javier
Abstract: We studied the prevalence of suicide attempts and cumulative incidence of completed suicide in schizophrenia (SZ), schizoaffective disorder (SZAF), delusional disorder (DD) and first-episode psychosis (FEP). A systematic review was performed using Scopus and PubMed databases (1990- July 2020). A random effects meta-analysis was conducted. Stratified analyses were conducted by diagnosis, clinical setting and geographical region. The prevalence of attempted suicide was 20.3% for SZ, 46.8% for SZAF, 11.1% for DD and 12.5% for FEP. Suicide attempts rates were higher for outpatient samples than for inpatient samples in SZ, SZAF and DD (but not FEP) studies. Analyses by geographical region in SZ showed greater prevalence of suicide attempts in North America and Northern Europe. The cumulative incidence of completed suicide was 2.0% for SZ, 2.4% for SZAF; 2.2% for DD and 1.9% for FEP. In schizophrenia and FEP studies, Northern European studies reported higher rates of completed suicide when compared to Western European countries. In conclusion, suicidal behaviour rates in psychoses differ by diagnoses, clinical setting and geographical region Highlights: We conducted a meta-analysis on suicide behaviour in psychotic disorders. Attempted suicide and completed suicide were considered. We compared suicide behaviour rates among psychotic subtypes. Patients with schizoaffective disorder reported higher rates of suicide behaviour. Suicide behavioural rates were higher in North America and Northern Europe.